Determinant Factors Of Financial Distress In Construction Companies: Moderation By Company Size - Miradji, Moh. Afrizal; Kamal, Irsyad; Sartika, Dewi; Purwanggono, Cuk Jaka; Setiawan, Iwan (LPPM ISNJ Bengkalis, 2024)
The purpose of this study is to investigate and evaluate the influence of intellectual capital (IC), debt-to-equity ratio (DER), and return on assets (ROA) on financial distress moderated by company size. This study uses a quantitative method with secondary data derived from financial reports obtained through the official website of the Indonesia Stock Exchange (IDX). Construction companies listed on the IDX 2017-2022 became the research population, and the sampling technique used purposive sampling to obtain 10 construction company sub-sector samples with 60 observation data. The data analysis technique uses panel data regression with the help of EViews 10 software. The results of this study indicate that intellectual capital, ROA, and company size have a positive effect, but DER has a negative effect on financial distress; company size is proven to be able to moderate the effect of intellectual capital and ROA on financial distress. Company size cannot moderate the effect between DER and financial distress. This research can complement existing theories and be a reference for future research on financial distress. This research can serve as a guide for companies that want to improve their performance and for investors who assess company performance to obtain investment certainty; in addition, the management of stock issuers can maintain good company performance to increase investor confidence sustainably.